Connexin43 and Bergmann glial gap junctions in cerebellar function - Tanaka, Mika; Yamaguchi, Kazuhiko; Tatsukawa, Tetsuya; Theis, Martin; Willecke, Klaus; Itohara, Shigeyoshi (Frontiers in Neuroscience, 2008)
Connexin43 (Cx43), a major component of astrocytic gap junctions, is abundantly expressed in Bergmann glial cells (BGCs) in the cerebellum, but the function of Cx43 in BGCs is largely unknown. BGCs are specialized astrocytes closely associated with Purkinje cells. Here, we review our recent studies of the role of Cx43 in gap junctional coupling between BGCs and in cerebellar function. We generated Cx43 conditional knockout mice with an S100b-Cre transgenic line (Cx43fl/fl:S100b-Cre), in which there was a significant postnatal loss of Cx43 in BGCs and cerebellar astrocytes. Gap junctional coupling between BGCs measured by dye coupling was virtually abolished in Cx43fl/fl:S100b-Cre mice. Electrophysiologic and behavioral analyses suggested that Cx43-mediated gap junctions and Cx43 hemichannels in BGCs are not necessary for the neuron-glia interactions required for cerebellum-dependent motor coordination and motor learning. These findings raise questions regarding the regional differences in the impact of the loss of Cx43 in the brain.